Outcomes of preterm neonates with patent ductus arteriosus: a retrospective review from a tertiary care hospital - Khowaja, Waqar; Akhtar, Saleem; Jiwani, Uswa; Mohsin, Muhammad; Shaheen, Fariha; Ariff, Shabina (Journal of the Pakistan Medical Association, 2022)
The management of patent ductus arteriosus (PDA) in preterm neonates remains controversial. A retrospective review was conducted to determine the outcomes in preterm neonates with PDA. Data of neonates admitted to the Aga Khan University Hospital from January 2012 to December 2016 were retrieved from patient records. Of the 208 neonates included in the study, 143 (68.7%) received no treatment, while 65 (31.2%) underwent pharmacotherapy and/or surgical ligation for PDA closure. PDA closure was spontaneous in 109 (52.4%) neonates. The mean ±SD gestational age (GA) of neonates with spontaneous ductal closure was greater as compared to those who required some form of treatment [33±3.3 vs 29.7±3.1weeks, p=0.001]. Apnoea (OR:4.47; 95% CI:1.21-16.44), sepsis (OR:3.81; 95% CI:1.33-10.87), pulmonary haemorrhage (OR:4.88; 95% CI:1.24-19.19), and lower APGAR (OR:0.69; 95% CI:0.54-0.90) were associated with higher odds of mortality in our cohort. Our findings demonstrate that PDA resolves spontaneously in most preterm neonates and provide evidence that conservative treatment is not associated with mortality. Keywords: Conservative treatment; ligation; mortality; patent ductus arteriosus; premature.